Association between Necrotizing Sialometaplasia and Smoking: An Integrative Review (Global Journal of Medical Research, 2023)
Necrotizing Sialometaplasia NS is a benign self-limiting rare inflammatory condition that involves the salivary glands tissues and simulates a malignant process The etiology of this lesion is still not fully understood The aim of this study was observe and evaluate the profile of this condition and its association with smoking This integrative review followed six methodological stages and evaluated only case reports published from 1973 to 2022 It was analyzed 134 cases which 25 of them were associated with smoking Others clinical features were also observed and described Although the NS is a rare condition it is necessary to know and understand so as not to confuse this lesion with a malignant neoplasm and apply inappropriate treatments that may impair the patient s quality of life
Keywords: salivary glands; diagnosis; tobacco; case reports